The Microbiome of Prostate Fluid Is Associated With Prostate Cancer - Ma, Xiaowei; Chi, Chenfei; Fan, Liancheng; Dong, Baijun; Shao, Xiaoguang; Xie, Shaowei; Li, Min; Xue, Wei (Frontiers in Microbiology, 2019)
Objectives: To explore the microbiome of the prostatic fluid in high-PSA patients. Patients and Methods: The microbiome profiles of prostatic fluid samples from 32 PCa patients and 27 non-PCa people were assessed. Microbiome analysis was assessed by massive 16S ribosomal RNA gene sequencing. Results: Compared with the NCA group, the microbial diversity was lower in the CA group. There were no specific microbial species in the CA group or NCA group. However, many species, such as those in the genera Alkaliphilus, Enterobacter, Lactococcus, Cronobacter, Carnobacterium, and Streptococcus, showed a significant difference between the CA group and NCA group. Conclusions: The prostate contains reduced bacteria, suggesting a possible pathophysiological correlation between the composition of the microbiome and PCa. Meanwhile, this study uncovered that the microbiome may be beneficial in maintaining the stability of the microenvironment of the prostate and provides interesting perspectives for the identification of novel biomarkers in high-PSA patients.